ANTIMICROBIAL SUSCEPTIBILITY OF LISTERIA ISOLATED FROM FOOD PRODUCTS - G. S. Skitovich; K. V. Serova; N. B. Shadrova; O. V. Pruntova (Ветеринария сегодня)
The paper demonstrates results of testing food products and raw materials for Listeria monocytogenes in 2011-2016. In 2011, the share of detected positive samples amounted to 0.3% (n=1100), in 2016 the detection level amounted to 7% (n=698). Basic types of products containing Listeria monocytogenes include meat and semi-finished meat products (87.2%; n=34), poultry meat and semi-finished poultry meat products (10.3%; n=4), and pasteurized cream (2.6%; n=1). The test results showed that all Listeria monocytogenes isolates demonstrated resistance to cephalosporins, aminoglycosides and fluroquinolones.